The Doctrine of Separation (Khōrismos) and Its Critique in Aristotle’s Metaphysics - Petuška, Virgilijus (Problemos, 2019)
[full article and abstract in Lithuanian; abstract in English]The paper deals with the concept of separation (khōrismos) and its criticism in Aristotle’s Metaphysics. More specifically, the paper aims to show that in the Metaphysics, Aristotle criticized the separation of Forms and the separation of numbers as two inextricably linked (rather than two separate and utterly unrelated) philosophical doctrines related to two distinct yet inherently connected cases of the same theoretical problem. This thesis is supported by the general thematic structure of books M and N, Aristotle’s testimonies regarding the genesis of the theory of Forms, as well as an interpretation of the latter according to the phenomenon of number, as it was understood by the ancient Greeks.
Keywords: Aristotle; Plato; Forms; numbers; separation